2002
DOI: 10.1007/s100670200013
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic Thrombocytopenic Purpura as an Initial Presentation of Primary Sjo¨gren’s Syndrome

Abstract: A healthy woman presented with ecchymoses due to thrombocytopenia, with numerous bone marrow megakaryocytes, microangiopathic haemolytic anaemia, disorientation, irritability, and normal renal function. Thrombotic thrombocytopenic purpura (TTP) was diagnosed and treated successfully by plasma exchange therapy, both on presentation and during a further three relapses. The TTP was considered idiopathic until, 4 months later, definite primary Sjogren's syndrome (1 degree SS) was diagnosed following the appearance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…To the best of our knowledge, the present case is the first report in the English language literature in which renal necrosis developed due to rapid onset of RVT in a patient with an autoimmune disorder and membranous nephropathy, which finally required nephrectomy. (7). In the present case there were no aggressive findings suggestive of TMA-like fragmented red blood cells,…”
Section: Discussionmentioning
confidence: 72%
“…To the best of our knowledge, the present case is the first report in the English language literature in which renal necrosis developed due to rapid onset of RVT in a patient with an autoimmune disorder and membranous nephropathy, which finally required nephrectomy. (7). In the present case there were no aggressive findings suggestive of TMA-like fragmented red blood cells,…”
Section: Discussionmentioning
confidence: 72%
“…A review of the literature revealed six other such cases (Table 1). 8,[25][26][27] Three (patients 1, 5, 7 in Table 1) of the total seven cases of TTP complicating SS (including ours) had cellular infiltration or immunological findings in the glomeruli. All three patients had a rapidly fatal course despite plasma exchange.…”
Section: Discussionmentioning
confidence: 93%
“…Multiple case reports have described the development of TTP in the background of SLE [9–11, 20, 21]. Similarly, there are cases of cooccurrence of Sjögren's syndrome and TTP [12, 2224]. One particular study investigated the prevalence of concurrent autoimmune disorders in 76 patients with TTP [13].…”
Section: Discussionmentioning
confidence: 99%